The synthesis of theory and practice in heritage studies - a way toward prosperity (Case study from Croatian ex-war area) - Babić, Darko muzeolog (Array, 2008)
After the war, in 1995, the revitalisation started but progressed slowly. During 2004 multidisciplinary group of experts initiated a heritage based project within the area. The core idea of the project is that the local, common heritage could be the main catalyst of the future regional development.